Improving literacy skills through writing Nusantara Poetry at an Nahdloh Tanjong Sepat Islamic Boarding School, Selangor, Malaysia - Sahri, Sahri; Anwar, Saeful; Pamungkas, Bakti Putra; Murod, Ahmad Kamal; Hasan, M. Ibnu (Institut Teknologi Dirgantara Adisutjipto, 2025)
This community service activity aims to improve literary literacy among students of An Nahdloh Islamic Boarding School, Tanjong Sepat, Selangor, Malaysia, through Nusantara poetry writing training. The background of this activity is based on the low interest and ability of students to appreciate and write literary works, even though the cultural potential and Islamic values they have are very rich and worthy of being raised in the form of poetry. This program is implemented through five main stages, namely: preparation, socialization, training, evaluation, and sustainability. The training is structured with a participatory and contextual approach, involving students in the creative process of writing, reading, and discussing poetry openly. The results of the evaluation showed a significant improvement in the understanding of the elements of poetry and the ability to write creatively. As a follow-up, the An Nahdloh Santri Literary Community was formed and the publication of a digital anthology